The diet of adult and chick rock shags (Phalacrocorax magellanicus) inferred from combined pellet and stable isotope analyses - Morgenthaler, Annick (2020)
The current information about the diet composition of the rock shag (Phalacrocorax magellanicus) in the SW Atlantic coast comes mainly from conventional pellet or stomach content analysis from a few locations situated in northern Patagonia (Chubut Province, Argentina). In this work, we studied the diet of breeding rock shags over several years at a colony from southern Patagonia (Ría Deseado, Santa Cruz Province, Argentina) using a combined technique of conventional diet assessment (pellet analysis) and stable isotope analysis of carbon and nitrogen. Our results confirm the importance of benthic prey and the low inter-annual variability in the diet of the rock shag. These results coincide with previous research in relation to the exploitation of slow moving, predictable, but low-energy density prey. The stable isotope mixing models, which was informed with prior data obtained from pellet analysis, allowed for the detection of subtle differences between the diet of adults and chicks, consisting in the incorporation of higher proportions of cephalopods, an energy-rich prey, in the diet of chicks. By comparing our results with the diet of the red-legged cormorant, which breeds in sympatry in the Ría Deseado Estuary and whose diet composition is strongly pelagic, we suspect a certain level of trophic resource partitioning between these rock shag and red-legged cormorant.